Superconductor Materials-A Revolutionary Value Addition to Space Electronics - Biswas, Rathindra Nath (Defence Science Journal, 2004)
An early success in low temperature superconductor technology has led to the development of a number of high temperature superconductor (H TS) materials, which have critical temperature above 77 K. When the temperature of a solid is lowered below critical temperature, the material loses its electrical resistivity. Because resistance is almost zero, superconductors can carry very high current, generating very large homogeneous magnetic fields. Due to these features, it is possible to design electronic devices with extremely thin profile, offering less weight and low manufacturing cost. Such exceptional properties have made HTS materials useful in military and space sectors, wherc airborne systems have already provided with cryogenic infrastructure which can he used for cooling a high temperature superconductor at no extra cost.